177 COUNTERREGULATORY HORMONES IN RATS TREATED WITH HEPATIC INSULIN GENE THERAPY FOR DIABETES. (1st January 2006) - Olson, D. E.; Campbell, A. G.; Jhia, D.; Lin, Y.; Thulé, P. M.
Abstract : Hepatic insulin gene therapy (HIGT) using a metabolically regulated insulin transgene expressed in the liver is an effective way to supply insulin to diabetic rats to maintain growth and normalize random daily blood glucose. Previous results in rodent models of diabetes support the role of transcriptional regulation of insulin secretion as part but not all of the mechanism that allows normal random daily blood glucose, improved glucose tolerance compared to diabetic rats, and the ability to tolerate extended fasts with blood glucose similar to nondiabetic rats. Glucagon was previously found to be uniquely elevated in the BB/Wor model of spontaneous autoimmune diabetes. We further explored the roles of counterregulatory hormones in the mechanism of glycemic control with HIGT. Sprague-Dawley rats were made diabetic with streptozotocin and treated with an adenovirus carrying a metabolically regulated insulin transgene that is expressed in the liver (Ad/(GlRE)3 BP1-2xFur, 2 3 10 10 PFU/kg). Glucagon, growth hormone, and cortisol were measured in HIGT-treated diabetic rats (DM + HIGT), diabetic rats treated with subcutaneous insulin (DM), nondiabetic rats treated with HIGT (non-DM + HIGT), and nondiabetic control rats (non-DM). HIGT-treated rats were also given long-acting octreotide analogues to block the release of glucagon and growth hormone while monitoring blood glucose, insulin, and counterregulatory hormones. Glucagon was found to be consistently and uniquely elevated in DM + HIGT-treated diabetic rats. Insulin levels were low in HIGT-treated rats. Growth hormone was elevated in all diabetic rats and cortisol was elevated in all rats tested. Blocking glucagon secretion with octreotide moderately decreased blood glucose levels in HIGT-treated rats examined during 12 hours of random feeding and during a fast. Novel methods of insulin administration may have important interactions with endogenous systems of glycemic control. Unique elevations in glucagon appear to have moderate effects to enhance the safety and efficacy of HIGT in diabetic rats by allowing physiologic controls in DM + HIGT and by interaction with the transgene promoter. Further evaluation of hepatic glucose handling as a result of HIGT and elevated levels of glucagon are expected to identify the mechanism of glycemic regulation in diabetic rats treated with metabolically regulated insulin transgenes expressed in the liver.